The Characteristics and Quality of Egg from Commercial Laying Hens Fed with Garlic (Allium Sativum) Supplemented Ration - Leke, Jein Rinny; Wantasen, Erwin; Sompie, Florencia; Elly, Femy Hadidjah; Siahan, Ratna (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The research aimed to determine the characteristics and quality of egg of commercial laying hens fed ration supplemented with garlic (Allium sativum) powder. The research used Completely Randomized Design (CRD) with five treatments and four replicates (5 hens each) for a total of 100 brown laying hens strain MB 402. Garlic powder contained 24.62% crude protein, 38.81% fat, and 1.74% crude fiber. The treatments of garlic powder ration were 0, 2, 4, 6, and 8%. The treatments performed were dietary, with R0 = 100% based diet (BD); R1= 98% based diet (BD) + 2% garlic meal (GM); R2= 96% based diet (BD) + 4% GM, R3 = 94% based diet (BD) + 6% GM, R4 = 92% based diet (BD) + 8% GM. The study was conducted during eight (8) weeks. Collected data were quality, weight, shell weight, albumen weight and shell thickness of eggs. Data was analyzed with Analysis of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT). The results showed that 8% garlic powder ration increased weight and albumen weight of eggs. There were no significant effect of treatments in yolk weight, shell weight and shell thickness of eggs. Garlic powder supplementation on laying hen ration affected egg weight and albumen weight. The addition of garlic powder on laying hen ration of up to 4% increased egg weight. Albumen weight increased until garlic powder supplementation of up to 8%. It is recommended the use of 8% garlic powder supplementation on lying hen ration without negative effects on egg quality.